Implications of Social Anxiety Disorder on the Improvement of Maharah Al-Kalam Arabic Students - Icha Gilang Permata, Icha Gilang Permata; Cahyono, Machrup Eko (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2023)
The goal of this research is to find out the implications of social anxiety disorder for the increase in maharah al-kalam of Arabic students, as well as to find out the factors that cause the emergence of social anxiety disorder in Arabic students and the symptoms it causes. This research is included in the type of qualitative research with the library research method. The documentation method is chosen by the author in data collection activities. Then, the collected data were analyzed using content analysis techniques. Research, the result is obtained that shows that social anxiety disorder has implications for increasing maharah al-kalam Arabic students. Some of the factors that cause social anxiety disorder in students include not having confidence in their abilities, fear of being wrong, worrying about the negative responses of others, inequality in economic status, addiction to social media, being born to permissive parents, and experiencing trauma. The symptoms include feeling uncomfortable, stiff movements, unfocused eyesight, body shaking, sensitivity, and avoiding eye contact. The results of this study have implications for Arabic language teachers to realize that social anxiety disorder experienced by students is not something that can be taken lightly and needs to be overcome, then so that teachers can take social anxiety disorder prevention measures for their students.